The impact of remote and hybrid work models on small and Medium-sized enterprises productivity: a systematic literature review - Maity, Richik; Lee, Khai Loon (Springer Nature, 2025)
This study undertakes a systematic literature review of the impact of remote and hybrid work models on the productivity of small and medium-sized enterprises in the post-COVID-19 environment. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses procedure, data were collected from Scopus and Web of Science, resulting in a final sample of 12 peer-reviewed studies published between 2020 and 2024 that were studied across diverse global contexts. The review finds that flexible work arrangements generally improve productivity by increasing employee satisfaction, reducing commuting time, and supporting work–life balance. Hybrid models emerged as the most effective, as they combine the independence of remote work with the collaborative advantages of in-person interaction, while also highlighting persistent challenges, including inadequate digital infrastructure, communication issues, and increasing cybersecurity risks in small and medium-sized enterprises. This study provides a comprehensive suggestion of critical success factors for small and medium-sized enterprises adapting to hybrid work models, offering valuable insights that can guide both small and medium-sized enterprises and policymakers. Overall, the review suggests that hybrid work models offer a sustainable path to improve productivity and flexibility, although further research is needed to evaluate long-term effects and regional differences.